2019
DOI: 10.1155/2019/5130835
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Evaluating Dredging Productivity Using a Data Envelopment Analysis‐Based Technique

Abstract: The increase in the frequency of extreme weather has caused the impact of natural disasters to become more extensive. Natural disasters reduce the effective storage capacity of reservoirs and affect their normal function. Reservoir dredging is a key issue in the management of water resources and is a complicated multiple-attribute decision-making (MADM) problem. The traditional assessment of dredging productivity has been performed using a labor productivity method to evaluate the related issues of dredging pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Charnes et al [12] initially introduced the DEA method as a mathematical programming method that can evaluate the relative efficiency of decision-making units (DMUs) (first-mode CCR model). DEA is a method that uses multiple inputs to produce multiple outputs to measure the relative efficiencies of a group of DMUs.…”
Section: Dea Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Charnes et al [12] initially introduced the DEA method as a mathematical programming method that can evaluate the relative efficiency of decision-making units (DMUs) (first-mode CCR model). DEA is a method that uses multiple inputs to produce multiple outputs to measure the relative efficiencies of a group of DMUs.…”
Section: Dea Methodsmentioning
confidence: 99%
“…On the other hand, the integrated fuzzy data envelopment analysis (FDEA) and fuzzy-multi attribute decision-making (F-MADM) were used to evaluate and select the safest airlines in Iran [11]. Some scholars used the novel DEA-based method to evaluate the dredging productivity of the national army and found that it can effectively address the complicated MADM problem of dredging productivity [12]. A complete picture of major airlines' operations can be achieved by exhaustively examining their efficiency in European airspace using the novel input/output parameters of the Data Envelope Analysis (DEA) [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e fuzzy-set-based methods and data envelopment analysis are commonly used approaches to solve complex MADM problems, such as [1]. us, many authors used a fuzzy-set-based approach to handle supply-chain-related issues under fuzzy information environments [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the developed sensor technology, more operational data have been gained for analyzing dredging performance. In the literature review, machine learning methods were recently adopted to model the complex and dynamical construction process of CSD (cutter suction dredger) for their excellent learning and mining ability [8]. Generally, the learning-based prediction models can be mainly divided into two main types based on the depth of structure: shallow learning models and deep learning models [9].…”
Section: Introductionmentioning
confidence: 99%